An iterated graph construction and periodic orbits of Hamiltonian delay equations - Albers, Peter; Frauenfelder, Urs; Schlenk, Felix (Journal of differential equations, 2019)
According to the Arnold conjectures and Floer's proofs, there are non-trivial lower bounds for the number of periodic solutions of Hamiltonian differential equations on a closed symplectic manifold whose symplectic form vanishes on spheres. We use an iterated graph construction and Lagrangian Floer homology to show that these lower bounds also hold for certain Hamiltonian delay equations.
Available online 23 August 2018
Gesehen am 25.01.2018